Testosterone and cardiometabolic risk in the general population - the impact of measurement method on risk associations: a comparative study between immunoassay and mass spectrometry - Haring, Robin; Baumeister, Sebastian E; Nauck, Matthias; Völzke, Henry; Keevil, Brian G; Brabant, Georg; Wallaschofski, Henri (European journal of endocrinology, 2013)
Low total testosterone (TT) serum concentrations in men have been associated with various cardiometabolic risk factors. But given error-prone immunoassays used for TT assessment, upcoming mass spectrometry methods question the validity of these risk associations. Thus, we performed the first comparative study quantifying potential differences in the association of TT with cardiometabolic risk factors between the two methods. We used data from 1512 men aged 20-81 years, recruited for the cross-sectional population-based Study of Health in Pomerania (SHIP), Germany. TT concentrations were repeatedly measured by chemiluminescent immunoassay (CLIA, Immulite 2500) and liquid chromatography-tandem mass spectrometry (LC-MS/MS). We tested for significant differences between coefficients from CLIA- and LC-MS/MS-based multiple linear regression models associating TT with major cardiometabolic risk factors including adiposity, lipid metabolism, blood pressure, diabetic status, and inflammation. TT measurements by CLIA and LCMS/MS yielded a pearson correlation coefficient of 0.84. only three of the ten tested associations for tt with cardiometabolic risk factor showed significant differences between the two measurement methods: in comparison to LC-MS/MS, CLIA-based TT assessment significantly underestimated risk associations of TT with waist circumference (β: -0.54 vs -0.63), BMI (β: -0.19 vs -0.22), and serum glucose levels (β: -0.006 vs -0.008). In this comparative study, the CLIA platform showed a reasonable measurement error and yielded comparable risk associations, providing little support to measure TT concentrations in men from the general population exclusively by LC-MS/MS.